Two roads diverged in a cell: insights from differential exosome regulation in polarized cells - Komori, Tadayuki; Fukuda, Mitsunori (Frontiers in Cell and Developmental Biology, 2024)
Exosomes are extracellular vesicles involved in intercellular signaling, carrying various cargo from microRNAs to metabolites and proteins. They are released by practically all cells and are highly heterogenous due to their origin and content. Several groups of exosomes are known to be involved in various pathological conditions including autoimmune, neurodegenerative, and infectious diseases as well as cancer, and therefore a substantial understanding of their biogenesis and release is crucial. Polarized cells display an array of specific functions originated from differentiated membrane trafficking systems and could lead to hints in untangling the complex process of exosomes. Indeed, recent advances have successfully revealed specific regulation pathways for releasing different subsets of exosomes from different sides of polarized epithelial cells, underscoring the importance of polarized cells in the field. Here we review current evidence on exosome biogenesis and release, especially in polarized cells, highlight the challenges that need to be combatted, and discuss potential applications related to exosomes of polarized-cell origin.